Triboelectric behaviors of inorganic Cs1−xAxPbBr3 halide perovskites toward enriching the triboelectric series. Issue 48 (16th November 2020) - Wang, Yudi; Yang, Xiya; Xu, Wenkai; Yu, Xueping; Duan, Jialong; Duan, Yanyan; Tang, Qunwei
Abstract : Inorganic perovskites are regarded as "star" semiconductors with unique ferroelectricity due to their superior triboelectric behaviors to those of state-of-the-art dielectric polymers when applied in a triboelectric nanogenerator (TENG). Abstract : Inorganic perovskites are regarded as "star" semiconductors with unique ferroelectricity due to their superior triboelectric behaviors to those of state-of-the-art dielectric polymers when applied in a triboelectric nanogenerator (TENG). An in-depth understanding on the charging mechanism of these inorganic halide perovskites may help design a robust TENG platform. Herein, alkali metal ion doped cesium lead tri-bromine Cs1− x A x PbBr3 (A = Li +, Na +, K +, and Ru +, x = 0–1) perovskites are systematically investigated concentrating on their triboelectric behaviors for the first time. The triboelectric charging affinities of these perovskites are ascertained by evaluating the electrical output performances and figures of merit of TENGs based on perovskite/poly(vinylidene fluoride) pairs in vertical contact-separation mode. Finally, a supplemented qualitative triboelectric series including Cs1− x A x PbBr3 perovskites is established regardless of the doping concentration, and can be utilized as a benchmark to guide the future dielectric selection for robust TENGs. This study not only casts light on the determination of an expanded triboelectric series, but also provides new insights into inorganic perovskites in the application of mechanical energy harvesting.